Redes de bragg em fibra óptica: análise de encapsulamentos em resposta à vibração e temperatura - Bastos, Talita Paes de (2016)
The sensors based on Bragg gratings in optical fibers have relevant characteristics such as their small size and the possibility of measuring accurately in a large number of parameters under various conditions. This work aims to analyze the study perspectives for different tunnels for the Bragg networks in the vibration and temperature measurements, seen separately. Comparisons are presented between Gel of oil, water, mineral oil and air. The results demonstrate the ability of the sensors to monitor the vibrational effects between 100 Hz and 450 Hz and temperature between 20 °C and 70 °C, pointing to gel encapsulation as a more stable sensor with greater signal clarity. Generating more in-depth study opportunity for the types of encapsulations and their applications in the various measurement environments.